2017
DOI: 10.1091/mbc.e16-10-0722
|View full text |Cite
|
Sign up to set email alerts
|

Vamp-7–dependent secretion at the immune synapse regulates antigen extraction and presentation in B-lymphocytes

Abstract: Extraction of immobilized antigens by B-cells relies on the fusion and secretion of lysosomes at the immune synapse. This process depends on the local recruitment of the SNARE protein Vamp-7 to the immune synapse, which is critical for B-cells to acquire their antigen presentation function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Two mechanisms have been proposed to promote the extraction of tethered antigens by B cells. While the first one involves B cell polarization and lysosome secretion within the synaptic cleft allowing the proteolytic extraction of the tethered antigens ( Obino et al., 2017 , Yuseff et al., 2011 ), the second one relies on cycles of B cell spreading and contraction coupled to mechanical extraction through pulling forces exerted by the motor protein Myosin II ( Fleire et al., 2006 , Harwood and Batista, 2011 , Natkanski et al., 2013 ). To determine which pathway was affected by Galectin-8, we first evaluated the ability of this lectin to induce B cell spreading.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two mechanisms have been proposed to promote the extraction of tethered antigens by B cells. While the first one involves B cell polarization and lysosome secretion within the synaptic cleft allowing the proteolytic extraction of the tethered antigens ( Obino et al., 2017 , Yuseff et al., 2011 ), the second one relies on cycles of B cell spreading and contraction coupled to mechanical extraction through pulling forces exerted by the motor protein Myosin II ( Fleire et al., 2006 , Harwood and Batista, 2011 , Natkanski et al., 2013 ). To determine which pathway was affected by Galectin-8, we first evaluated the ability of this lectin to induce B cell spreading.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, tethered antigens are extracted through lysosome and protease secretion when presented on rigid surfaces, whereas they are extracted through mechanical forces exerted by the motor protein Myosin II when presented on flexible surfaces such as the plasma membrane of antigen-presenting cells (Natkanski et al., 2013, Obino et al., 2017, Yuseff et al., 2011). However, stimulation of B cells in the presence of Galectin-8 did not trigger higher levels of MLC phosphorylation, an indicator of Myosin II activation (Figure S3F), suggesting that proteolytic rather than mechanical extraction of antigens is being reinforced under these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highlighted by the fact that Sec3 and Sec6, part of the exocyst complex, are able to modulate SNARE assembly at the membrane of yeast (Morgera et al, 2012; Shen et al, 2013; Yue et al, 2017). In B cells, defective lysosome secretion generated by silencing the SNARE protein Vamp7 also impairs the extraction and presentation of immobilized antigens (Obino et al, 2017). Whether Exo70 and/or other subunits of the exocyst complex interact with Vamp-7 to promote the docking of Vamp-7 + vesicles at the IS shall be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The first one is involved in many physiological processes, regarding either all cells, such as membrane repair, or specialized cell types, such as neurons for neurite growth or macrophages phagocytosis [ 117 ]. The secretion of lysosomes is fundamental for many specialized cell activities, such as antigen presentation in antigen presenting cells (APCs) [ 118 ], bone absorption in osteoclasts [ 119 ] and transmitter release [ 120 ] in neurons. Initially, lysosomal exocytosis was considered to be limited to these specialized secretory cells, but later, a few studies clearly indicated that this process occurs in all cell types [ 121 , 122 ].…”
Section: Lysosomal Exocytosis Associated Functionmentioning
confidence: 99%